Surface Distress Index Assessment and Google Earth Mapping of Road Conditions on the Rumbuk–Jantuk Road - Rizqi Mustofa Ahmad; Titik Wahyuningsih; Ari Ramadhan Hidayat (Universitas Medan Area, 2026)
Road pavement deterioration can reduce transportation serviceability, user comfort, and safety, particularly when damaged sections are not systematically identified and prioritized for maintenance. This study aimed to assess the pavement condition of the Rumbuk–Jantuk Road in East Lombok Regency using the Surface Distress Index (SDI) method and to spatially map the condition of each road segment using Google Earth. A descriptive quantitative approach was applied to a 1.5 km road section divided into 15 observation segments of 100 m. Field surveys recorded crack area, crack width, pothole occurrence, rutting, and geographic coordinates. The SDI values were calculated sequentially and used to classify pavement conditions into good, moderate, light damage, and severe damage. The results show considerable variation among segments, with SDI values ranging from 35 to 430. Based on the calculated SDI values, one segment was classified as good, two as moderate, one as light damage, and eleven as severe damage. The severe segments represent approximately 73.3% of the surveyed road length and require priority intervention. Google Earth mapping successfully visualized the spatial distribution of pavement conditions and facilitated the identification of maintenance priorities. The integration of SDI and digital mapping provides a practical basis for systematic road maintenance planning.